Practical Evaluation of LoRa under Co-Technology Interference - Elshabrawy, Tallal; Edward, Phoebe; Ashour, Mohamed; Robert, Jörg (IEEE Vehicular Technology Conference, 2020)
Recently, LoRa has established itself as one of the front runners of the Low Power Wide Area Network (LP-WAN) technologies. Due to the simple ALOHA-based medium access scheme adopted by LoRa, collisions between the transmitted LoRa packets are inevitable. Nevertheless, the patented LoRa modulation has inherent potential for strong capture capabilities to survive some co-technology interference. Most of the research activities investigating the LoRa capture effect have assumed the packet capture on the basis of a constant pre-set signal to interference ratio (SIR) threshold. On the other hand, a theoretical study based on simulations has shown that the SIR thresholds depend on the encountered signal to noise ratio (SNR). However, the practical demonstration of the joint relationship between the SIR and SNR is still lacking in the literature. In this paper, the practical evaluation of the LoRa under co-technology interference is investigated under various/controlled interference scenarios. The SIR, SNR as well as the relative delay between the interfering packets are controlled through our developed software-defined radio (SDR) testbed acting as transmitter. The commercial LoRa transceiver based on HopeRF RMF95 module is used as a receiver for the interfered signal. This LoRa transceiver is also used to record the received SNR, the successful capture rate (SCR) and the data extraction rate (DER). Results show that the SCR is significantly enhanced in case the relative delay corresponds to the preamble being free of interference. Unlike the SCR, the DER is affected by the experienced SIR in case of relative delay of 20.3symbols. Finally, the coverage region's curves show that in case of no interference an SNR threshold of -8.2 dB is required in order to guarantee a DER of 90%.
CRIS-Team Scopus Importer:2021-04-19
Keywords: Capture Effect; Coverage Regions; DER; LoRa Interference; SCR; SDR